CHARACTERIZATION OF LACTIC ACID BACTERIA ISOLATED FROM SUMBAWA MARE MILK - Sujaya, Nengah; Ramona, Yan; Widarini, Ni Putu; Suariani, Ni Putu; Utama Dwipayanti, Ni Made; Ayu Nocianitri, Komang; Nursini, Ni Wayan (Jurnal Veteriner, 2008)
A study was carried out to isolate and characterize lactic acid bacteria (LAB) from the Sumbawa mares milk The Isolation of LAB was conducted in Man Rogosa Sharpe (MRS) agar. The isolates were characterized by standard methods, such as Gram staining, cell morphology study and fermentation activities. The ability of the isolates to inhibit some pathogenic bacteria was studied by dual culture assay. Isolates showing the widest spectrum of inhibiting pathogenic bacteria were further identified using API 50 CHL. The results showed that Sumbawa mare milk was dominated by lactobacilli and weisella/leuconostoc. As many as 26 out 36 isolates belong to homofermentative lactobacilli and another 10 isolates belong to both heterofermentative lactobacilli and weissella or leuconostoc. Twenty four isolates inhibited the growth of Escherichia coli 25922, Shigela flexneri, Salmonella typhimurium, and Staphylococcus aureus 29213. Two promising isolates with the widest spectrum of inhibiting pathogenic bacteria, Lactobacillus sp. SKG34 and Lactobacillus sp. SKG49, were identified respectively as Lactobacillus rhamnosus SKG34 and Lactobacillus ramnosus SKG49. These two isolates were specific strains of the sumbawa mare milk and are very potential to be developed as probiotic for human.
Keywords: Sumbawa mare milk, lactic acid bacteria, Lactobacillus rhamnosus, probiotic